A literature analysis of the use of Absorptive Capacity construct in IS research - Gao, Shijia; Yeoh, William; Wong, Siew Fan *; Scheepers, Rens (Elsevier, 2017)
Since the seminal inception of Absorptive Capacity (ACAP) by Cohen and Levinthal (1990), it has been adopted widely in information systems (IS) research. This paper analyzes the use of ACAP in IS research through a literature analysis of ACAP-related papers published in 52 reputable IS journals from 1990 to 2015. Drawing on a review of the evolution of ACAP, the analyses conducted include: (1) descriptive analysis of ACAP in IS papers; (2) domains of ACAP usage; (3) analysis of hypotheses and propositions to show how ACAP is being used to explain various organizational phenomena in IS research; and (4) analysis of the measures to provide insights into the operationalization of ACAP in IS research. Our findings suggest that while the majority of the research correctly conceptualizes ACAP as a capability, various misalignments between ACAP conceptualization, operationalization and measurement, and the level of analysis in the literature continue to do a disservice to the accumulated research in ACAP. The findings and recommendations should help IS researchers to conceptualize and operationalize ACAP appropriately.